(untitled) (Research, Society and Development, 2020)
Reading the literary can be understood as an experience through which the reader is crossed and enables the constitution of knowledge that becomes incarnated in him/herself. In this paper, we seek to identify, in the field of Education, more specifically in the education of readers, in two databases, research whose theme is the reading of the literary as an experience, having as premise the listening of the reader: the Brazilian Digital Library of Theses and Dissertations - BDTD and the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel - CAPES, between the years of 2007 and 2017. The research points to an apparent enlarged look at the studies related to the reader of the literary, it shows that there are concerns about the constitution of the reader and his/her relationship with the text, what sense of incarnated reading is used by some authors and what sensitive knowledge reverberates when making an experience from reading the literary. In addition, it shows that the field lacks studies based on the experiences of reading the literary in a specific way; moreover, works that listen to the reader and to his/her experiences.